Meet the rabbis: rabbinic thought and the teachings of Jesus - Young, Brad (Hendrickson Publishers Inc., 2007)
Introduction to rabbinic thought -- Master teachers and their disciples -- Torah is more than law -- The Great Sanhedrin -- Parallel rabbinic and New Testament texts -- Introduction to early Jewish writings -- Ethics of the Fathers -- The Amidah prayer -- Maimonides' thirteen principles of Jewish faith -- Hillel's seven principles of biblical interpretation -- Meet the rabbis -- Both Torahs were revealed on Mount Sinai -- Utopia, or plan of action -- Of books, commandments, laws, holy days, and lineage